Saving Death: Apoptosis for Intervention in Transplantation and Autoimmunity. Issue 2 (2006) - Li, Alice; Ojogho, Okechukwu; Escher, Alan
Abstract : Long considered immunologically "bland, " apoptotic cells are now recognized as important modulators of immune responses. The role of apoptosis in immunological homeostasis has been inferred from several findings, for example, induction of tolerance after injection of apoptotic cells and the capacity of APCs like macrophages and DCs to induce and maintain tolerance after phagocytosis of dead cells. Processing of apoptotic cells by DCs is of particular interest, because DCs are the only known APCs capable of activating naïve T lymphocytes to become effector or regulatory cells. In that regard, recent evidence suggests that phagocytosis of apoptotic cells by DCs can induce Tregs, a finding that has significant implications for the treatment of a variety of immune-mediated inflammatory disorders. Here, we review the relationship between apoptotic cells, DCs, and Tregs, and its impact on prevention of transplant rejection and treatment of autoimmune diseases.